Effect of Eco-enzyme on Water Quality Parameters in Some Rivers Disembogued at Ambon Bay - Tuhumury, Novianty C.; Tuahatu, Juliana; Manuputty, Gratia D. (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Due to the increasing population in Ambon City, the high volume of organic waste in rivers that empties into Ambon Bay can impact the marine ecosystem. On the other hand, processing organic waste in the form of eco-enzymes has been widely applied and has benefits, for instance, as a cleaning liquid. This study aimed to analyze the effect of eco-enzyme concentrations on water quality parameters, such as pH, ammonia, detergent, coliform, nitrate, phosphate, BOD, COD, and DO in several rivers flowing into Ambon Bay. The research was conducted from May to November 2022. Water samples were collected from four rivers that flow into Ambon Bay. Production of ecoenzyme was carried out at the Marine Science Laboratory at Pattimura University for three months. Eco-enzyme derived from banana peels obtained from tourist areas on Ambon Island. The research applied the method of observation and experiment. The data of each parameter obtained from the treatments (sample before and after treatment using 10% and 20% of eco-enzyme) were then compared with Second-Class of River Water Quality Standards. The results showed that eco-enzyme could neutralize the pH value. The DO, ammonia, detergent and coliform concentration decreased after adding 10% and 20% of the eco-enzyme. By contrast, adding eco-enzyme to the river watercan increase the concentration of nitrate, phosphate, BOD, and COD.